2014
DOI: 10.1186/s12955-014-0156-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of EuroQoL-5 dimension (EQ-5D) and Short Form-6 dimension (SF-6D) among stable angina patients

Abstract: ObjectivesSeveral preference-based health-related quality of life (HRQoL) instruments have been published and widely used in different populations. However no consensus has emerged regarding the most appropriate instrument in therapeutic area of stable angina. This study compared and validated the psychometric properties of two generic preference-based instruments, the EQ-5D and SF-6D, among Chinese stable angina patients.MethodsConvergent validity of the EQ-5D and SF-6D was examined with eight a priori hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 48 publications
(68 reference statements)
4
33
0
1
Order By: Relevance
“…This is consistent with previous studies in mainland China. [27][28][29][30] Two facts may account for this finding. First, the survey participants lived a normal life at home, which implies better HRQOL than those who live in medical institutions for professional care.…”
Section: Discussionmentioning
confidence: 93%
“…This is consistent with previous studies in mainland China. [27][28][29][30] Two facts may account for this finding. First, the survey participants lived a normal life at home, which implies better HRQOL than those who live in medical institutions for professional care.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, QOL is a crucial research topic in China, particularly in recent years. Chinese researchers mainly focus on developing or improving the measurement tools based on the world’s popular tools and Chinese situations, such as SF-36, SF-12, SF-6D, WHOQOL and EQ-5D [48]. Researchers often use reliability and validity indicators to evaluate the effects of the developed or modified tools.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggested EQ‐5D was more efficient in detecting differences among subgroups with differing health status, while another study showed SF‐6D may be a more effective tool with lower ceiling effect and greater sensitivity . There were also a few studies showing Chinese patients with stable angina preferred SF‐6D, while older, chronically ill patients favored EQ‐5D …”
Section: Discussionmentioning
confidence: 99%